From global to local: Developing a context-specific BeSD-HPV tool through cultural and linguistic adaptation in Pakistan - Khola Noreen; Mehreen Noor; Saba Maryam; Mukhtiar Baig (PLoS ONE, 2026)
Objectives A key challenge in preventing cervical cancer is the low uptake of the Human Papillomavirus (HPV) vaccine in low and middle-income countries (LMICs). Evidence indicates that, in addition to logistical and structural issues, this is often influenced by sociocultural factors. The objective of this study was to develop a culturally adapted Behavioral and Social Drivers (BeSD) of HPV vaccination framework that is linguistically appropriate, contextually grounded, and culturally sensitive, to evaluate the social, behavioral, and cultural factors influencing HPV vaccination in Pakistan. Methods This descriptive qualitative survey was conducted across several districts in Punjab, Pakistan, from February to August 2025. Study participants included adolescent girls, parents/guardians, healthcare providers, community workers, teachers, school administrators, and religious scholars. Results Data were analyzed using Braun and Clarke’s six-step thematic analysis with deductive and inductive coding. Deductive codes aligned with existing WHO BeSD domains, while inductive analysis revealed a new domain: Cultural Integration. Themes and subthemes were mapped to specific BeSD constructs, illustrated with participant quotes and rationales. The tool was subsequently translated into Urdu by a bilingual expert to ensure linguistic appropriateness. Table cell colors correspond to the WHO BeSD domains (Thinking and Feeling, Social Processes, Motivation, Practical Issues) and the emergent theme, Cultural Integration. Conclusion The culturally adapted BeSD-HPV tool provides a methodological framework for contextualizing global health models. It underscores the need for culturally informed, community-driven strategies to ensure the successful rollout of HPV vaccination in Pakistan and other LMICs.